COMPREHENSIVE ANALYSIS OF GLOBAL DETERMINANTS OF FOOD SECURITY IN THE CONTEXT OF CURRENT CHALLENGES - ANDROSHCHUK, Ilona (Herald of Khmelnytskyi National University. Economic sciences, 2025)
The article presents a comprehensive analysis of the global determinants of food security under the contemporary challenges of the world economic environment. The essence, content, and interrelation of key factors shaping global food stability are revealed, including economic, political, demographic, ecological, technological, and social dimensions. It has been established that, in modern conditions, food security results from the combined effects of multidirectional processes - from military conflicts and climate disasters to structural shifts in global trade, the digitalization of the agricultural sector, and changing consumption models. Special attention is paid to the impact of the Russia-Ukraine war on the functioning of agricultural markets, the disruption of food and energy supply chains, and the resulting rise in prices, food shortages in certain regions, and increased global inequality. The study also explores the relationship between demographic transformations, urbanization, population aging, and the evolution of dietary models, which directly influence demand, nutritional structure, and food accessibility levels. It has been proven that modern food security risks are systemic in nature and require the formation of an integrated international strategy based on the principles of sustainable development, technological innovation, ecological balance, and social justice. Conceptual approaches are proposed to enhance the efficiency of the global food security system through improved monitoring mechanisms, international coordination, and the advancement of green technologies. The findings of this study can be applied to the development of strategic solutions for strengthening food security, adapting national economies to global risks, and ensuring long-term food resilience. The research emphasizes the importance of strengthening international cooperation and improving the mechanisms of global food governance to ensure equitable access to resources. It also highlights the necessity of integrating innovative technologies and digital platforms into agri-food systems to enhance their adaptability, transparency, and sustainability in the face of global uncertainty.